2001
DOI: 10.1095/biolreprod65.1.240
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Matrix Proteins on the Expression of Matrix Metalloproteinase-2, -9, and -14 and Tissue Inhibitors of Metalloproteinases in Human Cytotrophoblast Cells During the First Trimester1

Abstract: The activity of matrix metalloproteinases (MMPs) specifies the ability of the trophoblast cell to degrade extracellular matrix (ECM) substrates. Usually the process of normal human placentation involves a coordinated interaction between the fetal-derived trophoblast cells and their microenvironment in the uterus. In this study, the effects of ECM proteins on the expression of MMP-2, -9, and -14 (membrane-type MMP-1); and the production of tissue inhibitors of metalloproteinase (TIMP) types -1, -2, and -3 have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 39 publications
2
49
0
4
Order By: Relevance
“…Possible ligands for the integrins on the maternal surface include osteopontin, laminin, thrombospondin, and perlecan (Kimber & Spanswick 2000), and on the blastocyst, the oncofetal fibronectin, a protein restricted only to trophoblasts (Feinberg et al 1991, Craven et al 2000. In addition, in vitro studies have shown that a v b3 may also interact and activate specific matrix metalloproteinases in the extracellular matrix of the uterus (Xu et al 2001), thereby implicating integrins in the transition between attachment and epithelial cell penetration.…”
Section: Integrinsmentioning
confidence: 99%
“…Possible ligands for the integrins on the maternal surface include osteopontin, laminin, thrombospondin, and perlecan (Kimber & Spanswick 2000), and on the blastocyst, the oncofetal fibronectin, a protein restricted only to trophoblasts (Feinberg et al 1991, Craven et al 2000. In addition, in vitro studies have shown that a v b3 may also interact and activate specific matrix metalloproteinases in the extracellular matrix of the uterus (Xu et al 2001), thereby implicating integrins in the transition between attachment and epithelial cell penetration.…”
Section: Integrinsmentioning
confidence: 99%
“…As the cells lose their proliferative ability, they invade the uterine wall by expressing specific matrix metalloproteinases (MMPs; Xu et al 2001, Staun-Ram et al 2004. It has been demonstrated that VEGF and MMPs 2 and 9 may comprise a functional network regulating the invasive phenotype in a variety of cell types including trophoblast cells (Anteby et al 2004, Hollborn et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…We also asked whether such an invasion-specific methylation pattern in serum shows differences between women with normal pregnancies and women developing preeclampsia-a disease known to be accompanied by a disturbed invasion process in the first trimester (6 ). We chose a panel of three genes (CDH1, TIMP-3, and PTGS-2) known to play key roles in the invasion process of tumor cells (17)(18)(19), which are often regulated by promoter hypermethylation (20 -22 ), or in the invasion process of trophoblast cells (2,(23)(24)(25). We also chose one gene (BLT1) involved in the regulation of immune response and regulated by promoter hypermethylation (26 ).…”
Section: Dna Methylation Changes In Sera Of Women In Early Pregnancymentioning
confidence: 99%
“…From our point of view, the most important finding is the similarity between pregnant women and metastasized breast cancer patients in the methylation changes in genes that are known to be involved in metastasis and tumor cell invasion (17-19, 27, 28 ) or even in the invasion process of trophoblast cells (2,(23)(24)(25) and in the regulation of the immune response (26 ). As sera of those cancer patients without evidence of metastasis at the time of diagnosis lacked the methylation changes found in advanced breast cancer and pregnancy (Table 1), we speculate that the observed methylation pattern reflects DNA release from invasive cells, specifically trophoblast cells and tumor cells.…”
Section: Dna Methylation Changes In Sera Of Women In Early Pregnancymentioning
confidence: 99%